Impact of vegetarian restaurant experiences on pro-environmental eating behaviors: a sustainable tourism perspective - Wang, Yunhan; Zhu, Xuanyu; Shen, Beiyi (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe rapid rise of vegetarian tourism mirrors the global expansion of the plant-based food market. Despite this trend, limited research has explored how vegetarian restaurants influence consumers’ pro-environmental behaviors through sensory experiences and the dissemination of green knowledge.MethodsGuided by the Stimulus–Organism–Response (SOR) framework, this study developed and empirically tested a conceptual model linking sensory perception, perceived green knowledge, green mindfulness, eco-reflection, and environmentally friendly dietary behavior. A mixed-methods approach was adopted, combining qualitative exploration with a quantitative survey conducted among 615 diners at vegetarian restaurants in Shanghai.ResultsStructural equation modeling results indicated that sensory experience and perceived green knowledge significantly enhanced green mindfulness and eco-reflection, which in turn promoted environmentally friendly dietary behavior. Both direct and indirect pathways were significant, confirming the mediating roles of green mindfulness and eco-reflection within the SOR framework.DiscussionThese findings deepen theoretical understanding of sustainable consumption mechanisms in vegetarian dining contexts by identifying sensory and cognitive routes that foster pro-environmental dietary behavior. Practically, the results offer insights for vegetarian restaurant managers on designing sensory environments and educational strategies that encourage mindful eating and reduce food waste.